Validation of the Warrior Identity Scale in the Chicagoland Veterans Study. Issue 1 (2nd January 2018) - Lancaster, Steven L.; Kintzle, Sara; Castro, Carl A.
ABSTRACT: The present study examined the psychometric properties of a measure of military identity in a sample of U.S. military members. Confirmatory factor analysis provided additional support for the multidimensional nature of military identity. Correlational analyses indicated that the domains of military identity were strongly related to postdeployment adjustment as well as other indicators of psychosocial health. Of importance, the relationships between the subscales of identity and the outcome variables differed in strength and direction depending on the form of identity, which supports a multidimensional structure of military identity. Additional research is necessary to identify the most salient domains of identity as well as the clinical and theoretical implications of identity in the functioning of veterans.